2011
DOI: 10.1007/s00384-011-1340-3
|View full text |Cite
|
Sign up to set email alerts
|

Dukes C colorectal cancer: is the metastatic lymph node ratio important?

Abstract: Current evaluation of positive lymph nodes may not accurately stage Dukes C colorectal cancer. The assessment of the LNR is a useful prognostic method in this heterogenous group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Therefore, we picked 142 stage III colon cancer patients from a cohort of 939 colorectal cancer patients who were operated on over a 10-year period. In comparison to other reports [6], the fraction, Stage III patients in comparison to all (I to IV) patients) is rather small but the number of examined lymph nodes is rather high [8,10] as is the percentage of patients receiving adjuvant chemotherapy [17]. …”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Therefore, we picked 142 stage III colon cancer patients from a cohort of 939 colorectal cancer patients who were operated on over a 10-year period. In comparison to other reports [6], the fraction, Stage III patients in comparison to all (I to IV) patients) is rather small but the number of examined lymph nodes is rather high [8,10] as is the percentage of patients receiving adjuvant chemotherapy [17]. …”
Section: Discussionmentioning
confidence: 72%
“…By doing so, there is no superiority in predicting disease-free and overall survival of the lymph node ratio to the N category of the TNM system. Other authors split patient cohorts by random or percentiles rather than calculating groups [6,7,9,11]. By using more groups, the lymph node ratio gains in precision of prognosis [6,7,11], but if more subgroups were established in the N category, precision would presumably rise there as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study, Thomas et al performed a multivariate analysis to find out independent prognostic factors in 1098 patients, which had undergone colorectal cancer resections. They concluded that the presence of positive lymph nodes may not be an accurate indicator for stage III colorectal cancer; and the evaluation of ratio of lymph nodes is a more important prognostic factor in these patients (35). Various cut-off points were considered for the total examined lymph nodes (range 6-40) and lymph nodes ratio (range 0.07-0.69) by researchers in the literature (13 , 36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many recent studies investigated the prognostic impact of total lymph node identified and ratio of lymph nodes in resected colorectal cancer [2,9]. In another review, Ghahramani et al [10] found the higher number of assessed lymph nodes as a favorable prognostic factor for overall survival in 10 out of 11 studies on node negative colorectal cancer.…”
Section: Editorialmentioning
confidence: 99%